Peran Milenial Dalam Melejitkan Literasi Koperasi Syariah Di Revolusi Industri 4,0. - Kurnia Sandi Panjaitan; Muhammad Arif (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to provide an overview in the form of a portrait of the role of millennials in boosting sharia cooperative literacy in industry 4.0. This is done to be aware of Islamic law, including sharia-based cooperatives. The method used in this journal is the method used in this paper is descriptive analysis or in the language of 'Ulum Al-Quran it is called the tafsir tahlili method. Literacy culture is understood as science and civilization. Islam highly values ​​science and knowledge. Sharia cooperative literacy is very important, especially for millennials. This article aims to find out Do the Al-Qur'an and Hadith as the holy books of Muslims have strong roots? and has the potential to encourage followers to engage in sharia cooperative literacy, especially among millennials. In Industry 4.0, the use of social media is increasingly sophisticated. It is not only used for communication purposes but has been used for gaining knowledge, preaching content and so on.